Labor heterogeneity and the pattern of trade - Cebreros Zurita Carlos Alfonso (Banco de México, 2018)
This article combines data on trade flows with a novel construction of the distribution of skill in the population, based on the results from the International Adult Literacy Survey of the OECD, to evaluate the empirical importance of the distribution of talent as a determinant of the sectoral pattern of trade. It is found that both the mean and standard deviation of the distribution of skills are significant determinants of the pattern of trade. According to the results, cross-country differences in the distribution of skills explain more of the sectoral pattern of trade than differences in capital stocks and differences in indicators of a country's institutional framework.
Keywords: F12; F14; F16; J82; 330; comparative advantage; labor force composition; factor endowments; human capital